ANALISIS KESALAHAN SISWA DALAM PENYELESAIAN SOAL CERITA DITINJAU DARI TIPE KEPRIBADIAN KEIRSEY - Harvina Nur Zaeny; Sujiran; Dian Ratna Puspananda (Journal of Mathematics Education and Science, 2021)
This study has the aim of describing the types and factors of student errors in solving Social Arithmetic story problems in terms of Keirsey's personality type based on Polya's error analysis. This research includes qualitative descriptive research. The research instrument was questioned for classifying Keirsey's personality types, questions about Social Arithmetic stories, and interview guidelines. The technical analysis of the data carried out includes data reduction, data presentation, and drawing conclusions. The results showed that misunderstandings of seven problems were made by Artisan, Rational, and Idealist subjects. Artisan and rational subjects did not write what is known and asked in the problem completely. In the Idealist subject, write down what is asked in the question, but it is not quite right. Planning errors were made by the four personality type subjects, where they were not able to properly arrange the completion steps. Errors in carrying out the plan were made by the four personality type subjects, where the Guardian subject did not complete the completion step and miscalculated. Artisan and Idealist subjects did not write down the solution formula. At the same time, the Rational subject did not write conclusions and formulas in several steps of completion. Re-checking errors were carried out by the four personality type subjects, where the Guardian, Artisan, Rational, and Idealist subjects got the final result but were wrong. Rational subjects also do not perform calculations when checking again. On the other hand, the Idealist subject does not re-examine the solution obtained. Abstrak Penelitian ini memiliki tujuan yaitu mendeskripsikan jenis dan faktor kesalahan siswa dalam menyelesaikan soal cerita Aritmatika Sosial ditinjau dari tipe kepribadian Keirsey berdasarkan analisis kesalahan Polya. Penelitian1ini termasuk penelitian deskriptif kualitatif. Instrumen2penelitian berupa angket penggolongan tipe kepribadian3Keirsey, soal cerita aritmatika sosial dan pedoman wawancara. Teknis analisis2data mencakup pengurangan data, penyajian data dan penarikan kesimpulan. Hasil penelitian menunjukkan8bahwa kesalahan memahami7masalah dilakukan oleh subjek Artisan, Rational dan Idealist. Pada subjek Artisan dan rational tidak lengkap saat menuliskan apa yang diketahui dan ditanyakan dalam soal. Sedangkan subjek Idealist menuliskan apa yang ditanyakan dalam soal akan tetapi kurang tepat. Kesalahan menyusun rencana dilakukan keempat subjek tipe kepribadian, dimana mereka tidak mampu menyusun langkah penyelesaian dengan tepat. Kesalahan melaksanakan rencana dilakukan keempat subjek tipe kepribadian, dimana subjek Guardian tidak menyelesaikan langkah penyelesaian dan salah dalam perhitungan. Subjek Artisan dan Idealist tidak menuliskan rumus penyelesaian. Sedangkan subjek Rational tidak menuliskan kesimpulan dan rumus pada beberapa langkah penyelesaian. Kesalahan memeriksa kembali dilakukan keempat subjek tipe kepribadian, dimana subjek Guardian, Artisan, Rational dan Idealist memperoleh hasil akhir akan tetapi salah. Subjek Rational pula tidak melakukan perhitungan disaat memeriksa kembali. Sebaliknya subjek Idealist tidak memeriksa kembali penyelesaian yang diperoleh.